ANALISIS KETERSEDIAAN STOK BERAS TERHADAP HARGA BERAS DI DKI JAKARTA (STUDI KASUS: PASAR INDUK BERAS CIPINANG) - Lestiyanto Wibisono; . Arman; M. Rizal Taufikurohman (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2022)
This research was about the analysis of rice stocks availability on rice prices in DKI Jakarta. This study aims to identify determinants of rice stock in DKI Jakarta and determine the effect of rice stock availability on rice prices. The results of the identification of determinants of rice stock in DKI Jakarta using multiple linear regression showed that the variable (X3p) the initial rice stock of DKI Jakarta and the variable (X4p) the rice procurement of DKI Jakarta had a significant effect on the dependent variable (Yp) DKI Jakarta's rice stock. The results of the analysis of the effect of rice stock availability on rice price at the consumer level using simple linear regression with log-difference transformations showed that the variable dlog(Xp) the rice stock availability in DKI Jakarta had no significant effect on the dependent variable dlog(Yp) the rice price at the consumer level. The results of the analysis of the effect of rice stock availability on rice price at the producer level using simple linear regression with the Yp(-1) variable and the log-difference transformation showed that the variable dlog(Yp(-1)) the rice price at the producer level at lag 1 had a significant effect on the dependent variable dlog(Yp) the rice price at the producer level.